The effect of body Image perceptions on subjective wellbeing in adolescent students - Goh, Dion Yun Si (Nanyang Technological University, 2023)
This paper study the effect of body image perceptions on life satisfaction and emotional well-being in adolescents. It was found that the endogeneity of body image perceptions and associated biases in effect estimates are smaller when emotional well-being are not accounted for. Additionally, the effect estimates for gender differences are three times larger for females than males. A model to account for potentially endogenous variables was introduced and supplemented by the Instrumental Variable Estimation and Kinky Least Squares Estimation. As much research focuses on adults, it is worthwhile to find the relationship in adolescents. The results from this study can help with developing preventive measures targeted at minimising negative body image.